2009
DOI: 10.1021/ol901304y
|View full text |Cite
|
Sign up to set email alerts
|

Brevianamide J, A New Indole Alkaloid Dimer from FungusAspergillus versicolor

Abstract: Brevianamide J (1), a new indole alkaloid dimer, was isolated together with four new diketopiperazine alkaloids (brevianamide K-N, 2-5) from the solid-state fermented culture of Aspergillus versicolor. Their structures were elucidated on the basis of spectral data. X-ray crystallographic analysis confirmed the structures of 1 and 4.Diketopiperazine alkaloids, a class of important secondary metabolites, are widely found in fungi such as Aspergillus, 1 Penicillium, 2 Pestalotiopsis, 3 and Chromocleista. 4 This c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
61
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 9 publications
5
61
0
Order By: Relevance
“…Hence, the planar structure of 2 was assigned as shown in Figure 1. Brevianamide L, a structure reported recently, [9] shares the same planar structure of 2, but the configuration of C-12 differed in the two compounds. The relative configuration of brevianamide L was deduced by NOESY correlations between H-11 and H-2Ј/H-6Ј.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Hence, the planar structure of 2 was assigned as shown in Figure 1. Brevianamide L, a structure reported recently, [9] shares the same planar structure of 2, but the configuration of C-12 differed in the two compounds. The relative configuration of brevianamide L was deduced by NOESY correlations between H-11 and H-2Ј/H-6Ј.…”
Section: Resultsmentioning
confidence: 80%
“…Only six have been described: these are oxepinamide A-C, [8] cinereain, [10] janoxepin, [11] and brevianamide L. [9] All of these, except brevianamide L, have the same skeleton as that of oxepinamide D (1); brevianamide L shares the framework of compounds 2-4. It has been presumed that the biosynthesis of natural products featuring oxepin moieties proceeds through a thermal 6π electrocyclic ring opening of arene oxides.…”
mentioning
confidence: 99%
“…[8], and chromones such as aspergillitine or aspergiones A -F [9]. Our previous study on the alkaloidal metabolites of the fungus A. versicolor led to the identification of five new diketopiperazine alkaloids [10]. The present study disclosed four new diketopiperazine alkaloids, brevianamides O -R (1 -4, resp.…”
mentioning
confidence: 58%
“…The molecular formula (C 22 Table 1). The NMR data and the UV maxima at l max 209 (4.10), 248 (3.78), and 339 (3.53) nm suggested that compound 1 was an analog of brevianamide L [10]. The comparison of the NMR data of 1 with those of brevianamide L suggested that one O-bearing C-atom resonates at d(C) 84.5 in 1 instead of d(C) 70.4 in brevianamide L. The OH group must be located at C(3) in view of the key HMBCs of HÀC(17) and HÀC(18) with d(C) 84.5 (C(3)).…”
mentioning
confidence: 92%
See 1 more Smart Citation